Improving Student Learning Outcomes by Using Picture Media in Mathematics Learning in Elementary Schools - Evira Fajar Wicaksono (Jurnal Pendidikan Profesi Guru, 2023)
This study aims to analyze the increase in student learning outcomes in learning mathematics by using media images. This study used classroom action research which consisted of two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were third grade elementary school students. Data collection techniques used in this study were tests, observation and documentation. Data were analyzed using descriptive statistical techniques. The results showed that there was an increase in student learning outcomes in learning mathematics using media images. This is evidenced from the comparison of the results of cycle one and cycle two in this study. The average student learning outcomes in cycle one was 53 with a completeness percentage of 56%, while in cycle two the average student learning outcomes increased to 90 with a completeness percentage of 92%. Therefore, media images can be used as an alternative in overcoming the low learning outcomes of elementary school students in learning mathematics.